Analisis Faktor Risiko dengan Kejadian Penyakit Campak Di Kabupaten Boyolali - Ardiyanto, Bayu Septian; , Badar Kirwono, SKM, M.Kes; , Yuli Kusumawati, SKM,.M.Kes (Epid) (2016)
Measles was an infectious disease caused by a virus Paramixovirus, transmitted very easily through the air contaminated by droplets (spit) of infected people. Number of measles in Central Java as much as 0.61%, and in Boyolali were 33 cases. The purpose of this study was to determine the risk factors for measles in Boyolali. This research method using observational case control approach. The study population was a person who was recorded in the medical record that was in the Health Service Boyolali many as 49 people. Selection of sample cases by means of exhaustive sampling counted 49 people and to equalize the control group of age in the case group as many as 98 people. Bivariate analysis using chi square and multivariate analysis using logistic regression. The results of the bivariate analysis shows that there was a relationship between exclusive breastfeeding (OR 6,88, CI95% 2,683-17,639, p=0,001) and contact with patients (OR 30,40, CI95% 8,465-109,177, p=0,001) with the measles. While the results of multivariate analysis showed that the patient contact was a dominant factor in the occurrence of measles (OR 22.62 CI95% = 5.970 to 85.702, p = 0.001), meaning that people who have been in contact with measles patients at risk of contracting measles at 22.62 times